Resistência à tração dos componentes músculo-aponeuróticos na área doadora do retalho musculocutâneo transverso do reto do abdome - Vidal, Ronaldo [UNIFESP] (2010)
Introduction: The defect on the abdominal wall in the transverse rectus abdominis myocutaneos flap -TRAM flap- donor site is extensive, complex and predisposes the emergence of hernia, bulging and abdominal weakness. The closure of the abdominal wall must be anatomic and functional, preferably with autologous tissues, resistance synthesis material and minimal tension suture. The selective musculoaponeurotic undermining of the abdominal provide a abdominal wall closure with autologous tissue and reduced tension. Despite many clinical studies, no experimental researches prove the real efficacy of selective musculoaponeurotic undermining in the TRAM flap donor site. Objective: The aim of this study is to evaluate the resistance to medial traction of the musculoaponeurotic components in the bipedicled TRAM flap donor site. Methods: In the period of May of 2006 until May of 2008, 20 patients, with ages from 29 to 58 years old, submitted to mammary reconstruction with bipedicled TRAM flap were studied. The resistance to medial traction of the musculoaponeurotic components in the bipedicled TRAM flap donor site was measured with a dynamometer that was fixed in the lateral edge of the defect, 3 cm below the umbilicus. The traction coefficients obtained were compared in three situation: Initial Stage - with no incision or additional underminig in the flap donor site; Stage 1 - incision above the lateral edge of the rectus sheath; Stage 2 - undermining of the external oblique muscle. To the statistical analyses it was used the Wilcoxon and the t test to paired data in the comparison of the right and left traction coefficients in Initial Stage, Stage 1 and Stage 2. The Friedman test and the post hoc of Dunn test was used to compare traction coefficients in initial Stage, stage 1 and Stage 2, in the right and left sides. Results: There was a significant reduction of traction resistance after each stage of the dissection. Conclusion: The incision on the internal lateral edge of the rectus sheath and the external oblique undermining reduce the medial traction resistance of the musculoaponeurotic components in the TRAM flap donor site.